Effect of tillage and seeding density on Camelina sativa (L.) Crantz under a semi-arid climate - Seddik Benattia, Mohamed; Benniou, Ramdane; Mebarkia, Amar; Hannachi, Abderrahmane; Izountar, Dahbia; Dib, Mouna (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The Mediterranean Basin is warming at a rate approximately 20 % faster than the global average. In the southern Mediterranean countries, there is an urgent need to identify and adopt alternative crops that combine profitability with adaptability for local farmers. Camelina (Camelina sativa) has been proposed as a candidate for diversification. However, its agronomic performance under local semi-arid conditions remains poorly understood. To address this gap, a field study was conducted in the Setif region of Algeria over two growing seasons, examining the effects of three tillage systems (conventional tillage, minimum tillage, and direct seeding) and two seeding rates (600 and 800 seeds.m2). Results showed that tillage significantly impacted plant stand establishment, with the highest seedling emergence (436.28 plants.m-2) and final plant density at harvest (332.22 plants.m-2) obtained under conventional tillage. Seed yield was similar between conventional (120.74 g.m-2) and minimum tillage (106.94 g.m-2), and both systems significantly outperformed direct seeding (72.35 g.m-2). The growing season was identified as the predominant factor influencing the fatty acid composition of camelina oil, with α-linolenic acid ranging from 30.94 % to 35.22 % and oleic acid from 14.33 % to 18.82 %. These findings demonstrate that camelina is a resilient and promising oilseed crop capable of diversifying and strengthening agricultural systems in Algeria and similar semi-arid regions.